(untitled) (Scientia Agricola, 2013)
Soil organic carbon (SOC) is usually said to be well correlated with soil texture and soil aggregation. These relations generally suggest a physical and physicochemical protection of SOC within soil aggregates and on soil fine particles, respectively. Because there are few experimental evidences of these relations on tropical soils, we tested the relations of soil variables (SOC and soil aggregate contents, and soil texture) with the amount of SOC physically protected in aggregates on a set of 15 Malagasy soils. The soil texture, the SOC and water stable macroaggregate (MA) contents and the amount of SOC physically protected inside aggregates, calculated as the difference of C mineralized by crushed and intact aggregates, were characterized. The relation between these variables was established. SOC content was significantly correlated with soil texture (clay+fine silt fraction) and with soil MA amount while protected SOC content was not correlated with soil MA amount. This lack of correlation might be attributed to the highest importance of physicochemical protection of SOC which is demonstrated by the positive relation between SOC and clay+fine silt fraction.